Cost-effectiveness of Medical Expulsive Therapy with ?-blockers for Large Distal Ureteral Stones in China - Zhang, Yucong; Ouyang, Wei; Li, Heng; Liu, Haoran; Yuan, Peng; Lu, Hongyan; Sun, Xifeng; Ye, Zhangqun; Xing, Jinchun; Chen, Zhiqiang; Xu, Hua (Urology Journal, 2020)
Purpose: To assess the cost-effectiveness of medical expulsive therapy (MET) versus observation for large distal ureteral stones in China and provide preliminary evidence for the determination of the course of MET by mathematical estimation. Materials and Methods: With linear success rate assumptions, a decision tree was constructed by TreeAge Pro 2011 software. The stones passage rates after observation or receiving 0.4 mg daily tamsulosin were estimated according to a large randomized clinical trial (RCT). The costs of ureteroscopy, drugs and examinations were estimated according to related price from pharmacies or hospitals, or the guidance price published by the government. MET was also compared with observation by the sensitivity analysis. The effectiveness of MET or observation was presented by quality-adjusted life-day. Mathematical estimation of stone expulsion time was made by using a decision-analytic Markov model under the assumption that the daily stone expulsion probability is constant. Results: In China, the MET was associated with a $295.1 cost advantage over observation. The cost of ureteroscopy has to decrease to $77.8 to reach cost equivalence between observation and MET. Observation is cost-effective only if ureteroscopy is very cheap or the difference of stone expulsion rates is insignificant. The estimated expulsion time was much longer than those reported in above mentioned RCT. Conclusion: Due to the high cost of ureteroscopy, MET showed a cost advantage over observation in treating distal ureteral stones in China. The daily stone passage rate was inconstant. More studies are needed to find the appropriate duration of MET.